VALORIZAREA PĂCII ȘI A CREDINȚEI ÎN MEDIA STUDIU DE CAZ: BLACK CLOVER (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
The Valorisation of Peace and Faith in Media: A Case Study of Black Clover.This study explores the representation of peace and faith in contemporary media, focusing on the anime Black Clover. A bibliographic analysis of research on peace and media was conducted, revealing that discussions often centre around conflict and power. Using insights from the analysis, the study identifies the potential of Black Clover to convey Christian values such as peace, justice, and faith through its characters and narrative. The anime is positioned as a modern tool for evangelism and ethical reflection, offering a unique approach to spiritual teachings in the digital age. By examining Black Clover, the research demonstrates how media can engage contemporary audiences with deeper moral and religious themes, suggesting that anime holds potential for reshaping narratives of peace and faith in an increasingly media-driven society.